1976
DOI: 10.1007/bf00293439
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and some properties of a mammalian ribosomal DNA

Abstract: The DNA coding for 28 S and 18 S ribosomal RNA, including the spacer regions, has been isolated from calf (Bos taurus) thymus gland. The method used included shearing of the total DNA to a highly homogeneous size population, selective heat denaturation and S1 nuclease treatment to remove single stranded DNA. Repeated centrifugation on density gradients yields a 140-fold purified rDNA fraction with a GC content of 61.2% Eco RI nuclease cleaves this DNA into two fragments of 16.4 and 4.9 X 10(6) daltons. Hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Concerning the significance of minor components, so far, we have evidence from hybridization experiments that the 1.71 9-g/cm3 minor component contains ribosomal cistrons (M. Meunier, personal communication), in agreement with an independent report by other authors [8]. It is possible that other minor components may well correspond to other repetitive genes.…”
Section: Minor Componentssupporting
confidence: 89%
“…Concerning the significance of minor components, so far, we have evidence from hybridization experiments that the 1.71 9-g/cm3 minor component contains ribosomal cistrons (M. Meunier, personal communication), in agreement with an independent report by other authors [8]. It is possible that other minor components may well correspond to other repetitive genes.…”
Section: Minor Componentssupporting
confidence: 89%
“…Genomic DNA was extracted from peripheral leucocytes using standard phenol/chloroform extraction and precipitation with ethanol (Blin et al. ). The DNA concentration was determined by ultraviolet light spectrophotometry at 260 nm.…”
Section: Methodsmentioning
confidence: 99%
“…A 10-ml sample of peripheral blood was collected into EDTA coated vacutainer tubes by a standard venipuncture method from each subject. Genomic DNA was extracted from peripheral leucocytes using standard phenol/chloroform extraction and precipitation with ethanol (Blin et al 1976). The DNA concentration was determined by ultraviolet light spectrophotometry at 260 nm.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The number of rRNA genes also varies: in mice it is about 100 (Gaubatz et al 1975), in Rattus norvegicus -about 100-360 (Melli et al 1971), and in the cat -about 1000 (Szabo et al 1978). Although many details of rRNA gene organization in mammals remain unknown, it has been found that the size of repetitive units in them is about twice as great as it is in the case of amphibians (16.2-21.3x106 and 8x106 daltons respectively) (Southern 1975;Blin et al 1976;Arnheim and Southern 1977;Stambroock 1978;Meunier-Rotival et al 1979). As in amphibians, the absolute size of rDNA repeating units in mammals can also vary, due to variations in spacer length (Arnheim and Southern 1977;Stambroock 1978;Krystal and Arnheim 1978).…”
Section: Rdna Structure and Transcription In Amphibiansmentioning
confidence: 95%